Model JEES untuk Mendorong Peningkatan Kinerja Melalui Kesejahteraan Karyawan Usaha Kecil di Industri Makanan Ringan di Malang Raya - Robbie, R Iqbal; Ambarwati, Titiek (ICON Publisher, 2025)
The aim of this research is to determine the effect of employee well-being on employee performance, engagement and job satisfaction, the effect of satisfaction on performance, the effect of work involvement on performance and the effect of job satisfaction and involvement as mediation between well-being and employee performance in food SMEs in Malang Raya. This research uses a quantitative approach. The sample used was 220 employees but only 167 questionnaires were filled in by employees who worked in food SMEs. Data collection techniques through interviews and questionnaires. Data Analysis Method uses Scale Range Analysis and Data Processing Using the Smart PLS Version 4.0 Software Program. The results of this research are that well-being has a positive and significant effect on employee performance, engagement and job satisfaction and the influence of engagement on performance and satisfaction with performance also has positive and significant results. The questionnaire was not filled in completely by all respondents